Monetary unions and national welfare - Cem Görgün (Koç University-TÜSIAD Economic Research Forum (ERF), 2019)
This paper studies monetary regime choice between monetary union and flexible exchange rate regime in a large open economy framework. The classical approach emphasizes that monetary unions are inherently costly because a single interest rate cannot respond effectively to different shocks of members of the union. Therefore, it is argued that countries with similar shocks should establish a monetary union so that the cost of one-size-fits-all monetary policy is minimized. This study reveals that when there are inefficient shocks (namely those which distort the economy asymmetrically and break the 'divine coincidence') and countries are large, the classical approach fails. In that case, monetary regime choice should depend on relative variation (mean preserving spread) of inefficient shocks rather than proximity of shocks. A union implicitly imposes cooperation in monetary policy between its members. This cooperation improves response to foreign inefficient shocks while it worsens responses to domestic inefficient shocks slightly less in terms of domestic welfare. Therefore, a country chooses monetary union over flexible exchange rate regime if variation of foreign shocks is close to or larger than variation of domestic shocks. That is on the condition that losing exchange rate flexibility is not costly or has a small cost. In this way, the domestic country 'ties the hand of the foreign country' and prevents foreign monetary policy actions which hurt domestic welfare. Both countries benefit from cooperation provided by the union, if variances (spreads) of domestic and foreign shocks are close enough. Then, a monetary union becomes Pareto Improvement. How close variances should be so that monetary union is welfare increasing or Pareto Improvement, and welfare loss or gain of losing exchange rate flexibility are contingent upon price rigidity and trade elasticity.
Keywords: E52; E58; F33; F41; F42; 330; monetary unions; exible exchange rate; monetary policy; national welfare